2019
DOI: 10.1108/pr-11-2017-0345
|View full text |Cite
|
Sign up to set email alerts
|

From first impressions to selection decisions

Abstract: Purpose The purpose of this paper is to investigate how individual interviewers’ dispositional cognitive motivations may influence interview interactions and outcomes. More specifically, this study explores the influence of the need for cognition, need for cognitive closure, and accountability on the relationship between first impressions and selection decisions. Design/methodology/approach In total, 41 graduate students were assigned the role of interviewers and were tasked to interview 331 undergraduate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Content cues generally reflect the quality, type, and substance of information first transmitted by the displayer (Cober et al, 2004). Many studies concerned with content cues conceptualize them generally as the quality of messages displayed initially, and use holistic evaluations of either perceivers or objective evaluators to identify whether differences in displayed information content relate to future outcomes (Baum et al, 2016; Florea et al, 2019; Weisband, 1992). Additionally, content cues have been operationalized as the quantity of content cues (Williamson et al, 2010), the quality of cues (Chen et al, 2009), or a combination of both (Gatewood et al, 1993).…”
Section: Toward An Integrative Fundamental Elements Frameworkmentioning
confidence: 99%
“…Content cues generally reflect the quality, type, and substance of information first transmitted by the displayer (Cober et al, 2004). Many studies concerned with content cues conceptualize them generally as the quality of messages displayed initially, and use holistic evaluations of either perceivers or objective evaluators to identify whether differences in displayed information content relate to future outcomes (Baum et al, 2016; Florea et al, 2019; Weisband, 1992). Additionally, content cues have been operationalized as the quantity of content cues (Williamson et al, 2010), the quality of cues (Chen et al, 2009), or a combination of both (Gatewood et al, 1993).…”
Section: Toward An Integrative Fundamental Elements Frameworkmentioning
confidence: 99%
“…We are aware that the personnel selection process is not exclusively based on facial appearance and that gender inequality is a result of more complex processes. However, it is now demonstrated that evaluators, especially under time pressure and cognitive load, rely on judgmental shortcuts, easily available cues, and lay theories that are misperceived to be predictive of job performance (e.g., Florea et al, 2019). For this reason, early impressions from facial appearance would very likely affect the final hiring decision.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…For example, Levashina and colleagues (2014) discuss how "rapport-building" can contaminate the validity of interviews. Similarly, Florea et al (2019) explain how initial perceptions of an interviewee can skew selection decisions depending on the interviewer's cognitive motivation.…”
Section: Do Team Members Rely On Accurate Performance Predictions In ...mentioning
confidence: 99%